World Bank Research Digest, Vol. 11(3) - World Bank (World Bank, Washington, DC, 2019)
This issue includes the following headings: Are Active Labor Market Programs Effective in Developing Countries?; Are Automation and Trade Polarizing Developing Country Labor Markets, Too?; How Does Innovation Affect Employment in Developing Countries?; How Is the Internet Reshaping Work?; Big Data from Online Job Portals; The Motherhood Penalty and Female Employment in Urban India; How Some Female Entrepreneurs in Africa Enter Male-Dominated Sectors; Can Wage Subsidies Boost Employment in the Wake of an Economic Crisis?; Understanding the Effects of the World'sLargest Workfare Program; How Do Cities in Ethiopia Create Jobs?; What Is Behind the Decline in Wage Inequality in Latin America?; and Global Talent Flows.